Роль ротового дыхания, в возникновении зубочелюстно-лицевых аномалий и деформаций, нарушении сроков формирования соматического и психического развития ортодонтических пациентов - Аблязов, А.Р.; Сысоев, Н.П.; Зубкова, Л.П. (Таврический медико-биологический вестник, 2011)
On the basis of the spent clinical and functional methods of researches, from 100 orthodontic patients surveyed by us, at the age from six till seventeen years with anomalies of a bite, at carrying out of functional respiratory test, tests on a delay of breath after the maximum breath (test to the Bar) or after the maximum exhalation (test of Gencha) it has been defined that the mixed type of breath is revealed at 78 of 100, and oral at 22 patients. At 67 patients with sagittal anomalies of a bite time of a delay of breath for a breath is less than norm: at distal bite it makes (22,77-24,32) seconds, at mezial bite – (19,6 – 20,3) seconds. On an exhalation this indicator is equal at distal bite (13,9 – 14,5) seconds, at mezial bite – (11,1-11,8) seconds. Р ≤ 0,5.